2011
DOI: 10.1149/1.3512990
|View full text |Cite
|
Sign up to set email alerts
|

Ultra Shallow Arsenic Junctions in Germanium Formed by Millisecond Laser Annealing

Abstract: Millisecond laser annealing is used to fabricate ultra shallow arsenic junctions in preamorphized and crystalline germanium, with peak temperatures up to 900°C. At this temperature, As indiffusion is observed while yielding an electrically active concentration up to 5.0 ϫ 10 19 cm −3 for a junction depth of 31 nm. Ge preamorphization and the consecutive solid phase epitaxial regrowth are shown to result in less diffusion and increased electrical activation. The recrystallization of the amorphized Ge layer duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Similarly, high concentrations of electrically active As and Sb were obtained by laser annealing of As-and Sb-implanted Ge. 89 The short laser anneals favor solid phase epitaxial regrowth (SPER), i.e., the recrystallization of Ge layers that were amorphized by ion implantation either beforehand by means of Ge implantation or by dopant implantation itself. In particular, laser annealing is advantageous as even structural defects can be removed that are hardly dissolved by conventional thermal treatments (see, e.g., Bruno et al…”
Section: B Experimental Evidence For Donor Deactivationmentioning
confidence: 99%
“…Similarly, high concentrations of electrically active As and Sb were obtained by laser annealing of As-and Sb-implanted Ge. 89 The short laser anneals favor solid phase epitaxial regrowth (SPER), i.e., the recrystallization of Ge layers that were amorphized by ion implantation either beforehand by means of Ge implantation or by dopant implantation itself. In particular, laser annealing is advantageous as even structural defects can be removed that are hardly dissolved by conventional thermal treatments (see, e.g., Bruno et al…”
Section: B Experimental Evidence For Donor Deactivationmentioning
confidence: 99%
“…Choosing the S/D architecture depends on ρ c , but also on dopant activation and diffusivity. The best reported active concentrations for P, As, and Sb are >10 20 , 5×10 19 , and >10 20 cm -3 respectively [20], [21], [22]. However the difference in P, As, and Sb diffusivities (D) is far more significant.…”
Section: Methodsmentioning
confidence: 99%
“…Almost all literature dopant studies describe ion implanted B, Ga, P, As, or Sb into bulk Ge substrates. For the n-type dopants, the shallowest profiles have been produced by 5 keV As implants [72]. For the p-type dopants, the shallowest profiles have been produced by 2 keV B implants [73].…”
Section: Access Resistance 51 Doping Optimisationmentioning
confidence: 99%
“…It has been demonstrated that dopant activation and contact resistance can be dramatically improved by LTA in the melt regime [72,[93][94][95][96][97][98]. Control of melt-depth is done by changing laser energy density.…”
Section: Access Resistance 51 Doping Optimisationmentioning
confidence: 99%